The Novel 5-Fluorouracil Loaded Ruthenium-based Nanocarriers Enhanced Anticancer and Apoptotic Efficiency while Reducing Multidrug Resistance in Colorectal Cancer Cells - Danisman-Kalindemirtas, Ferdane; Ozerkan, Dilsad; Kariper, Ishak Afsin; Bulut, Huri (Springer Science and Business Media LLC, 2023)
Recently, nanocarriers have been made to eliminate the disadvantages of chemotherapeutic agents by nanocarriers. Nanocarriers show their efficacy through their targeted and controlled release. In this study, 5-fluorouracil (5FU) was loaded into ruthenium (Ru)-based nanocarrier (5FU-RuNPs) for the first time to eliminate the disadvantages of 5FU, and its cytotoxic and apoptotic effects on HCT116 colorectal cancer cells were compared with free 5FU. 5FU-RuNPs with a size of approximately 100 nm showed a 2.61-fold higher cytotoxic effect compared to free 5FU. Apoptotic cells were detected by Hoechst/propidium iodide double staining, and the expression levels of BAX/Bcl-2 and p53 proteins, in which apoptosis occurred intrinsically, were revealed. In addition, 5FU-RuNPs was also found to reduce multidrug resistance (MDR) according to BCRP/ABCG2 gene expression levels. When all the results were evaluated, the fact that Ru-based nanocarriers alone did not cause cytotoxicity proved that they were ideal nanocarriers. Moreover, 5FU-RuNPs did not show any significant effect on the cell viability of normal human epithelial cell lines BEAS-2B. Consequently, the 5FU-RuNPs synthesized for the first time may be ideal candidates for cancer treatment because they can minimize the potential drawbacks of free 5FU.
Keywords: Colorectal Cancer; Ruthenium-Based Nanoparticles; Cytotoxicity; Antineoplastic Agents; Apoptosis; HCT116 Cells; Ruthenium; Neoplasm Proteins; Cell Line, Tumor; Humans; ATP Binding Cassette Transporter, Subfamily G, Member 2; Fluorouracil; Colorectal Neoplasms; fu; 3. Good health